Kynurenine metabolism and inflammation-induced depressed mood: A human experimental study. (November 2019) - Kruse, Jennifer L.; Cho, Joshua Hyong-Jin; Olmstead, Richard; Hwang, Lin; Faull, Kym; Eisenberger, Naomi I.; Irwin, Michael R.
Highlights: Experimental inflammatory challenge acutely increases plasma levels of kynurenine pathway measures in humans. Changes in plasma kynurenine and quinolinic acid positively correlate with inflammation-induced depressed mood. Kynurenine metabolism may be a pathway linking inflammation and depressed mood. Abstract: Inflammation has an important physiological influence on mood and behavior. Kynurenine metabolism is hypothesized to be a pathway linking inflammation and depressed mood, in part through the impact of kynurenine metabolites on glutamate neurotransmission in the central nervous system. This study evaluated whether the circulating concentrations of kynurenine and related compounds change acutely in response to an inflammatory challenge (endotoxin administration) in a human model of inflammation-induced depressed mood, and whether such metabolite changes relate to mood change. Adults (n = 115) were randomized to receive endotoxin or placebo. Mood (Profile of Mood States), plasma cytokine (interleukin-6, tumor necrosis factor-α) and metabolite (kynurenine, tryptophan, kynurenic acid, quinolinic acid) concentrations were repeatedly measured before the intervention, and at 2 and 6 h post-intervention. Linear mixed models were used to evaluate relationships between mood, kynurenine and related compounds, and cytokines. Kynurenine, kynurenic acid, and tryptophan (but not quinolinic acid) concentrations changed acutely (p's all <0.001) in response to endotoxin as compared to placebo. Neither kynurenine, kynurenic acid nor tryptophan concentrations were correlated at baseline with cytokine concentrations, but all three were significantly correlated with cytokine concentrations over time in response to endotoxin. Quinolinic acid concentrations were not correlated with cytokine concentrations either before or following endotoxin treatment. In those who received endotoxin, kynurenine (p = 0.049) and quinolinic acid (p = 0.03) positively correlated with depressed mood, although these findings would not survive correction for multiple testing. Changes in tryptophan and kynurenine pathway metabolites did not mediate the relationship between cytokines and depressed mood. Further work is necessary to clarify the pathways leading from inflammation to depressed mood in humans.